2002
DOI: 10.1016/s1010-7940(01)01039-9
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoaneurysm of subclavian artery 21-years after staged repair of tetralogy of Fallot

Abstract: Three cases of pseudoaneurysm of subclavian artery in long-term follow-up after staged repair of tetralogy of Fallot are described. The angiographical study revealed that aneurysms were located in the systemic end area of previously ligated modified Blalock-Taussing shunt. Aneurysmectomy with resection of a shunt and segment of subclavian artery was performed. We believe division of a prosthetic shunt should be routinely performed during complete repair of tetralogy to prevent morbidity in the long-term follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…In one reported case, Demyanchuk et al detected a pseudoaneurysm a long period of time after the shunt operation, and they suggested that the main cause was that the relatively short shunt did not grow simultaneously with the somatic growth of the patient. 3 In our case 1, lung computerized tomography showed that the left subclavian artery was associated with the pseudoaneurysm. In case 2, based on our experiences, we first performed cardiac catheterization.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…In one reported case, Demyanchuk et al detected a pseudoaneurysm a long period of time after the shunt operation, and they suggested that the main cause was that the relatively short shunt did not grow simultaneously with the somatic growth of the patient. 3 In our case 1, lung computerized tomography showed that the left subclavian artery was associated with the pseudoaneurysm. In case 2, based on our experiences, we first performed cardiac catheterization.…”
Section: Discussionmentioning
confidence: 49%
“…In one reported case, Demyanchuk et al detected a pseudoaneurysm a long period of time after the shunt operation, and they suggested that the main cause was that the relatively short shunt did not grow simultaneously with the somatic growth of the patient. 3…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pseudoaneurysm formation is one of the rare but potentially fatal complications of SPSs and may be associated with shunt occlusion, infection, arterial or graft-related structural weakness, and dehiscence. The adverse events related to pseudoaneurysm may generated from rupture or compression and collapsing effect on the mediastinal structures and underlying lung parenchyma (81)(82)(83)(84)(85). Surgery is the traditional treatment, yet it may be associated with high morbidity and mortality, particularly in critically ill patients or those with active bleeding.…”
Section: Stent Implantation For Pseudoaneurysm Of Shuntmentioning
confidence: 99%
“…2 These catheterization-injury-related pseudoaneurysms are usually located at or distal to the subclavianevertebral junctions, 2 and endovascular strategy is the treatment of choice in modern practice. 5 They can also occur as a consequence of shoulder dislocation, 14 local balloon dilatation, 15 BlalockeTaussing shunting, 16 or type IV EhlerseDanlos syndrome. 17 It may also follow infection of previously placed stents.…”
Section: Discussionmentioning
confidence: 99%